Diagnostic value of ultrasonographic features in breast cancer and its correlation with hormone receptor expression - Yang, Jingzhou; Yu, Xiaojuan; Liu, Jianxin (Frontiers in Oncology, 2025)
IntroductionThe objective of this research is to investigate the diagnostic value of Ultrasonographic characteristics in breast cancer (BC) and its relation to hormone receptor status.MethodPatients who underwent Breast Neoplasm surgery from January 2020 to December 2022 were included, 68 patients with malignant and 40 patients with benign, based on pathological diagnosis as the reference standard. Each patient volunteered for an elastography imaging examination, and one lesion was evaluated for each patient.ResultsPatients had with mean age of 53.57 years (± 6.34), and lesion diameters ranged from 0.53-2.5 cm (1.29 cm ± 0.41). Kappa consistency analysis examined the inter-observer reliability of ultrasound elasticity signs in discriminating malignant from benign neoplasms. The correlation between ultrasonographic features and hormone receptor activity was also determined using Spearman correlation. Possible factors for having malignant BC lesions were tested, and binary logistic regression was utilized to develop the nomogram prediction model. There the malignant and benign groups were statistically significant in terms of ER, PR, Ki-67, HER-2 expression, marginal burrs, calcification foci, lesion diameter, and blood flow signal grading (P-levels < 0.05). The results of elastography indicated substantial concordance with pathological diagnosis (kappa = 0.875; P < 0.01). Statistically significant, positive correlations between breast cancer lesion diameter and Ki-67, burr sign and ER, as well as blood flow signal grading with PR, ER, Ki-67 and HER-2 were also observed. The independent predictors of malignancy in multivariate analysis included calcifications burr sign blood flow grading elasticity score ER and HER-2 (P < 0.05). By analyzing comprehensive clinical characteristics and measuring the total score as 263 points, the nomogram model achieved high validity in predicting the malignancy of breast lesions and could be applied in daily work with a 74.12% predicted probability of malignancy.DiscussionThe performance of ultrasound elastography is promising for BC diagnosis, and the association with hormone receptor status is highly significant. Further confirming that the elasticity score has significant clinical value for the diagnosis of malignant breast lesions, in addition to the fact that hormone receptor levels are independent of elasticity score, we can conclude that the elasticity score and hormone receptor levels are two distinct factors for malignant lesions.